2014
DOI: 10.1016/j.chom.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Polarity Proteins Participate in Innate Immunity to Pseudomonas aeruginosa Infection

Abstract: Summary The mucosal epithelium consists of polarized cells with distinct apical and basolateral membranes that serve as functional and physical barriers to the organisms’ exterior. The apical surface of the epithelium constitutes the first point of contact between mucosal pathogens, such as Pseudomonas aeruginosa, and their host. We observed that binding of P. aeruginosa aggregates to the apical surface of polarized cells leads to the striking formation of an actin-rich membrane protrusion with ‘inverted’ pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…The reasons for this discrepancy are not readily apparent, but different species and tissue origins of the cells used may be contributing factors. Another study recently demonstrated that polarity proteins, including PAR3, are required for NF-B induction in MDCK cells exposed to Pseudomonas aeruginosa (56). When P. aeruginosa touches the apical membrane, it induces membrane protrusions that have basolateral characteristics, with PAR3 localizing to the boundary of the normal membrane and the basal-like protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy are not readily apparent, but different species and tissue origins of the cells used may be contributing factors. Another study recently demonstrated that polarity proteins, including PAR3, are required for NF-B induction in MDCK cells exposed to Pseudomonas aeruginosa (56). When P. aeruginosa touches the apical membrane, it induces membrane protrusions that have basolateral characteristics, with PAR3 localizing to the boundary of the normal membrane and the basal-like protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly appreciated, however, that microbial interactions with the host epithelium and cell-cell junctions are not restricted to mechanical disruption of barrier function (39,41). Mounting evidence illustrates that bacteria can actively modulate other important aspects of junction function, such as altering cell polarity (42)(43)(44) and intracellular signals emanating from the junctions (45)(46)(47). Our findings build importantly on these observations, revealing not only that S. aureus α-toxin does target the junctions but also that α-toxin acts through adherens junctions components to mediate its cytotoxicity.…”
Section: Plekha7 Contributes To the Severity Of Mrsa Skin And Pneumoniamentioning
confidence: 99%
“…We specifically chose transient transfection because of its low efficiency in MDCK cells, resulting in “mosaic” monolayers in which a few transfected cells were surrounded by untransfected cells. This approach allowed us to closely mimic bacterial infections in which P. aeruginosa forms bacterial aggregates on the apical surface of only a small fraction of cells (Tran et al , 2014). …”
Section: Resultsmentioning
confidence: 99%
“…This change in membrane structure is dependent upon the activity and recruitment of the polarity protein Par3, phosphatidylinositol 3-kinase (PI3K), and the small GTPase Rac1. Remarkably, protrusion formation is associated with localized activation of the innate immune response, suggesting that the innate immune system may detect changes in cell polarity (Tran et al , 2014). Similarly, Neisseria meningitidis , an important cause of fatal meningitis, recruits polarity proteins, including Par3, to the apical membrane of endothelial cells leading to the formation of an ectopic junction underneath N. meningitidis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation